Peningkatan Keterampilan Membaca Siswa Kelas I Melalui Syllabic Methode di Sekolah Dasar - Rimadhani, Ariska; Kristin, Firosalia (Universitas Ngudi Waluyo, 2024)
The aim of this study is to improve the reading skills of first-grade students at Mangunsari 02 Public Elementary School through the syllabic method. This research employs a classroom action research approach, conducted in two cycles, involving stages such as planning, implementation, observation, and reflection. The subjects of this study consist of 4 female students and 8 male students from the first grade of Mangunsari 02 Public Elementary School in Salatiga City. Data collection is done through tests and non-tests. The data analysis involves both quantitative and qualitative descriptive data. The results of this study indicate that the syllabic method can enhance the reading skills of students, as evidenced by improvement in each cycle. Initially, there were only 2 students with proficient reading skills, accounting for 17%. In the first cycle, there was an increase in reading skills, with 5 students achieving proficiency, accounting for 33%. In the second cycle, there was further improvement, with a percentage of 75%, where 9 students had achieved proficient reading skills. The syllabic method proves to be effective in improving reading skills for first-grade students at Mangunsari 02 Public Elementary School. This can be seen from the resolved issues and improvements that occur in each cycle through the application of the syllabic method. It is hoped that teachers can implement the syllabic method as well as other teaching methods to support students in overcoming reading difficulties and other challenges in learning. Abstrak Tujuan dari penelitian ini adalah untuk meningkatkan kemampuan membaca siswa kelas I di SD Negeri Mangunsari 02 melalui penerapan metode syllabic. Jenis penelitian ini menggunakan pendekatan tindakan kelas dengan dua siklus, yang meliputi tahapan perencanaan, pelaksanaan, pengamatan, dan refleksi. Subjek penelitian terdiri dari 4 siswa perempuan dan 8 siswa laki-laki di kelas I SD Negeri Mangunsari 02 Kota Salatiga. Data dikumpulkan melalui tes dan penilaian non-tes. Analisis data dilakukan dengan menggunakan metode deskriptif kuantitatif dan kualitatif. Hasil dari penelitian ini menunjukkan bahwa penggunaan metode syllabic efektif dalam meningkatkan kemampuan membaca siswa, yang terbukti dari peningkatan yang terjadi pada setiap siklus. Pada awal penelitian, hanya 2 siswa yang memiliki kemampuan membaca baik, dengan presentase sebesar 17%. Pada siklus pertama, terjadi peningkatan kemampuan membaca, dengan 5 siswa mencapai tingkat kemampuan membaca yang baik, dengan presentase sebesar 33%. Pada siklus kedua, terjadi peningkatan lebih lanjut, dengan presentase mencapai 75%, di mana 9 siswa telah mencapai tingkat kemampuan membaca yang baik. Metode syllabic terbukti dapat meningkatkan kemampuan membaca pada siswa kelas I di SD Negeri Mangunsari 02. Hal ini tercermin dari penyelesaian masalah yang terjadi dan peningkatan yang terjadi pada setiap siklus melalui penerapan metode syllabic. Diharapkan bahwa guru dapat mengadopsi metode syllabic dan metode pembelajaran lainnya untuk mendukung siswa dalam mengatasi kesulitan dalam membaca dan pembelajaran secara umum.